The Relationship Between Sensory Attributes of Beverages and Change in Acylated Ghrelin Concentrations. (29th May 2020) - Evenson, Alexa; Heying, Emily; Barnett, Joleen; Widmer, Annaliese
Abstract: Objectives: To investigate sensory attributes of carbonated, flavored, and sweetened beverage consumption, and relationship to the hunger hormone, acylated ghrelin. Methods: In a randomized single-blinded crossover design, males ( n  = 14) and females ( n  = 15); aged 23–65; BMI < 30 kg/m 2 ; with no reported chronic disease consumed six different beverages (water, carbonated no flavor [CNF], carbonated lime flavor [CL], degassed lime flavor [DL], carbonated lime flavor with aspartame [CLS], and degassed lime flavor with aspartame [DLS]) at separate time points. Participants were asked to consume a breakfast meal (approximately 400 kcals) and then fast for approximately 4 hours. Blood was collected via finger-stick at baseline; and 10 and 45 minutes after consumption of the beverage. ELISA was used to determine acylated ghrelin concentration. A 7-pt likert scale was used to determine acceptability of the treatment beverages. ANOVA and spearman rank-order correlation coefficients were used to determine differences in liking of sensory attributes between beverages and correlations between variables, respectively. Results: The CNF, CL, and water beverages were well liked by participants with mean overall liking scores of greater than 5. The overall liking scores were not significantly different between these three beverages ( P > 0.05). There were significant differences between CNF, CL, and water and the remaining 3 beverages – DL, CLS, and DLS. Degassed and sweetened beverages (DL, CLS, and DLS) were least liked with mean liking scores ranging from 3.69–4.28. There were no significant correlations ( P > 0.05) found between change in acylated ghrelin concentration and overall liking or liking of beverage attributes. Conclusions: Acceptability of sensory attributes, including carbonation, flavor, and sweetness, was not related to change in acylated ghrelin concentrations after the consumption of six different beverages. Funding Sources: This work was funded by the College of Saint Benedict/Saint John's University Faculty Research/Development Grant.